PERAN PERAWAT DALAM APLIKASI INTERVENSI DISTRES SPIRITUAL (DUKUNGAN SPIRITUAL DAN DUKUNGAN EMOSIONAL) PADA PASIEN - Nur Ainiyah; Anggun Avivatul Fadllah (Coping: Community of Publishing in Nursing, 2021)
Phenomenon in the field shows there are patients who experience Spiritual Distress, but in providing care related problems of the patient, nurses usually do not apply intervenstion spiritual distress maximally. The purpose of this research was to get description of the role of nurses in the application of intervention spiritual distress (spiritual support and emotional support) to the patient in the inpatient rooms at Hospital A. The design of this research was Descriptive. The population in this study was nurses who work at Hospital A. amount 50 respondents. The sample in this research was 50 respondents. Sampling technique was Total Sampling. The variables in this study was description of the role of nurses in the application of intervention Spiritual Distress (Spiritual Support and Emotional Support) in Patients. The instrument was the questionnaire, furthermore the data was analyzed by descriptive statistics. The research finding showed that the role of 50 respondents nurses to overcome the problem of Spiritual Distress in the inpatient room at Hospital A., most (62%) had less role and almost half (38%) had a good role in the application of intervention spiritual distress. Conclusions of this research that the majority of nurses in the inpatient room are largely lack of role in application of spiritual distress. Therefore, hopefully that the nurse will prioritize the comprehensive biological-psychological-social-spiritual nursing more, to apply the management based on implementation guidance book especially on spiritual problem.